Very High Spatial Resolution Soil Moisture Observation of Heterogeneous Subarctic Catchment Using Nonlocal Averaging and Multitemporal SAR Data - Manninen, Terhikki; Jaaskelainen, Emmihenna; Lohila, Annalea; Korkiakoski, Mika; Räsänen, Aleksi; Virtanen, Tarmo; Muhic, Filip; Marttila, Hannu; Ala-Aho, Pertti; Markovaara-Koivisto, Mira; Liwata-Kenttala, Pauliina; Sutinen, Raimo; et al.
2021